IMPLEMENTASI PERDA NOMOR 13 TAHUN 2012 TENTANG RETRIBUSI JASA USAHA PELAYANAN PELABUHAN DALAM UPAYA MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN KEPULAUAN MERANTI - Muttaqin, Addinul; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Publication of regional policy (Perda No. 13 Tahun 2012) in Meranti Archipelago Regency aims to efforted and managed of levies port sector in this area. The regional policy implemented by local government through the transportation department of communication and informatics. Publication of regional policy (No. 13 tahun 2012) was â€œlegal protectionâ€ to regulate the activities in the harbor like unloading goods at the location of the port which are prohibited, the officers who did not provide admission and not wearing the attribute to provide services of levies port bussines service collection.The resourchers used teoretical concept is implementation policy by widjaya explained that the implementation of the policy is process of transforming the contents of policy (regional policy) into practice or implementation. The method used in this research is descriptive qualitative data collection instruments include observation and interview on local regulations No. 13 tahun 2012 and business services users port or compulsory levies as well as documentation and literature study related to the research objective.The result of this study indicate that the implementation is not optimal. The implementation of levy charges field the amount of levy collected variegated or not according to the principles stated in the determination of the structure of the local regulations. This is because the procedures for collecting the levy still found the levy charged for admission and do not use attributes that affect the activities of community and order port that impact or local revenue receipts in the sector of port levy.Key Word: Regional Policy, Implementation, Levy, Regional Achievement (PAD).